Seminoma I Stadio: Strategie a Confronto. Issue 3 (July 2013) - Tana, Silvia; Avuzzi, Barbara
Testicular cancer is an infrequent disease, accounting for 1% to 2% of all malignant neoplasms in men. However, it represents the most common solid malignancy among men between 15 and 35 years old. The standard initial treatment for stage I seminoma is radical inguinal orchiectomy. Since the mid-20 th century, the traditional treatment after surgery had consisted in external photon beam radiotherapy directed to the para-aortic and pelvic lymph nodes. Patients receiving radiotherapy achieve cause-specific survival rates approaching 100%, with virtually no relapses within the radiation portal. At the moment, the options for the management of stage I seminoma consist of surveillance, adjuvant radiation therapy and adjuvant chemotherapy usually done with carboplatin. Patients should be informed of all treatment options and of potential benefits and side effects of each choice. Significant treatment-related morbidities following radiotherapy have been reported. Acute toxicities are generally mild and self-timing, but patients treated with adjuvant radiotherapy alone had a significantly increased risk of second primary malignances (SPMs) and gonadal toxicity. The Medical Research Council (MRC) TE10 and TE18 randomized trials have investigated the reduction of the treatment volume and total dose to decrease the risk of radiation-related side effects. The MRC TE19 randomized trial compared radiotherapy and a single course of carboplatin AUC7. The preliminary results, reported in 2005, and also the updated results, reported in 2008 and 2011, confirm the non inferiority of single-dose carboplatin.